UHPLC‐Q‐TOF‐MS/MS Dereplication to Identify Chemical Constituents of Hedera helix Leaves in Vietnam - Hong Ngoc Pham; Chieu An Tran; Thi Diep Trinh; Ngoc Lan Nguyen Thi; Huynh Nhu Tran Phan; Van Nhan Le; Ngoc Hung Le; Van Trung Phung (Journal of Analytical Methods in Chemistry)
Hedera helix has been reported to contain a wide range of metabolites and produce many pharmacological effects. This research demonstrates the determination and evaluation of the phytochemical profiling of H. helix grown in central Vietnam. Methanolic extract of ivy had been analyzed by ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC‐Q‐TOF‐MS/MS). MS, and MS/MS experiments were manipulated using both negative and positive ionization modes to provide molecular mass information and production spectra for the structural elucidation of compounds. A total of 46 compounds including 24 triterpene saponins and other compounds were successfully identified of which four established saponin structures have been reported for the first time. This study has provided a base for building a quality control of the raw materials according to the profile of triterpene saponins and assessment of pharmaceutical ingredients of H. helix planted in Vietnam.